A tool for evaluating urban sustainability via integrated transportation and land use simulation models - Maoh, Hannah; Kanaroglou, Pavlos (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2009)
AbstractThis paper is focused on developing a simulation tool that will be used to assess urban sustainability and inform the future of urban planning. The tool is developed as an add-on module in an operational integrated transportation and land use model (ITLUM) calibrated for two Canadian cities: Hamilton, Ontario and Halifax, Nova Scotia. Progress towards sustainability is gauged based on indicators that will minimize negative environmental and social impacts while maximizing economic benefits. To this end, the methods to model the sustainability indicators are highlighted and described. A simulation example is provided to demonstrate the operability of the devised tool.